Structure Elucidation of a Melam–Melem Adduct by a Combined Approach of Synchrotron X‐ray Diffraction and DFT Calculations. Issue 35 (24th May 2019) - Kessler, Fabian K.; Burow, Asbjörn M.; Savasci, Gökcen; Rosenthal, Tobias; Schultz, Peter; Wirnhier, Eva; Oeckler, Oliver; Ochsenfeld, Christian; Schnick, Wolfgang
Abstract: Melam‐melem (1:1), an adduct compound that can be obtained from dicyandiamide in autoclave reactions at 450 °C and elevated ammonia pressure, had previously been described based on mass spectrometry and NMR spectroscopy, but only incompletely characterized. The crystal structure of this compound has now been elucidated by means of synchrotron microfocus diffraction and subsequent quantum‐chemical structure optimization applying DFT methods. The structure was refined in triclinic space group P 1 ‾ based on X‐ray data. Cell parameters of a =4.56(2), b =19.34(8), c =21.58(11) Å, α =73.34(11)°, β =89.1(2)°, and γ =88.4(2)° were experimentally obtained. The resulting cell volumes agree with the DFT optimized value to within 7 %. Molecular units in the structure form stacks that are interconnected by a vast array of hydrogen bridge interactions. Remarkably large melam dihedral angles of 48.4° were found that allow melam to interact with melem molecules from different stack layers, thus forming a 3D network. π‐stacking interactions appear to play no major role in this structure. Abstract : Twist my melon : Melam‐melem (1:1), an intermediate in the formation of heptazines from triazines, was structurally elucidated using synchrotron X‐ray diffraction. The obtained structure was optimized via quantum‐chemical calculations and the hydrogen bond network of the adduct compound investigated.